The Effect of the Non-Cognitive Factor Academic Persistence on Task as A Predictor of Students Academic Productivity in Universities in Cameroon - Neba Vernat Neh; Joseph Lah Lo-oh; Zinkeng Martina (Researchparks Publishing, 2021)
Academic persistence on task being a modifiable individual non-cognitive aspect is the degree to which students feel compelled to pursue the goals needed to finish their current level of studies, regardless of the difficulties and obstacles they face. This study aimed to examine the effect of the non-cognitive factor academic persistence on task as a predictor of students’ academic productivity in universities in Cameroon; the study employed a mixed method research design; a sample of 443 postgraduate students of six faculties, three in the University of Buea and three in the University of Bamenda were used. Results indicate that, academic persistence on task predict university students academic productivity. Significant, positive and relatively moderate relationship was detected between academic persistence on task and academic productivity with P-value <0.001, far <0.05. The findings of the correlation coefficient (R=0.280**) indicates that academic productivity significantly increased with increase in academic persistence on task. Contribution of the study includes praising students’ efforts and not outcome in order to build persistence. The study recommends to teachers on how to help strengthen the persistence of struggling learners by reinforcing effort and not outcome; Stressing peer modeling and teaching struggling learners to make greater effort. The limited empirical work addressing the relationship between academic persistence and students’ academic productivity posed a significant limitation to the study. Larger studies using more diverse samples are needed to more clearly delineate relationships between academic persistence on task and university students academic productivity. Furthermore, further studies should address how the interrelations or lack of persistence on task change as student graduate from University.